Soybean Evaluation of Inoculation: A Three-Year Summary - M. A. Secchi; T. M. Albuquerque; O. A. Ortez; G. I. Carmona; J. Kimball; E. A. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2018)
The relationships between soybean (Glycine max) seed yield and response to nitrogen (N) fertilization have received considerable coverage in scientific literature. This project aims to quantify the response to inoculation for soybean in a field without previous history of this crop (20 years). To address this objective, field studies were conducted during the 2015, 2016, and 2017 growing seasons at the East Central Experiment Field, Ottawa, KS. The treatments consisted of five different N-management approaches: non-inoculated (NI), inoculation at the recommended commercial rate (I1), a double rate of inoculation (I2), a triple rate of inoculation (I3), and non-inoculated but fertilized with 300 lb of N/a (NF). In the 2015 growing season, yields did not statistically differ from one another. In the 2016 growing season, treatment differences were observed and seed yield ranged from 36 to 59 bu/a. In the 2017 growing season, treatments showed significant yield difference, with yields ranging from 23 to 52 bu/a, from the NI to the NF treatment, respectively. Further research should be carried out to understand the impact of the inoculation practice and better understand the best management for N in soybean in newly-planted areas.
Keywords: Inoculation; soybean; nitrogen management